Expert system and its capabilities / Muthukkaruppan Annamalai - Annamalai, Muthukkaruppan (Universiti Teknologi MARA Cawangan Pahang, 1989)
The approach towards development of fifth generation computers is going to be a remarkable turning point in the information technology because of the emergence of computers with enhanced intelligence is anticipated. Systems that are capable of image processing, computer aided design, computer aided manufacturing are harbingers of the fifth generation computer applications. In time to come, with many aspirations of the fifth generation computers coming true, it will render the present day conventional computers and its associated procedural programming techniques, obsolete in many fields. One of the biggest areas in which this new breed of computers will be used is Artificial Intelligence (AI). Conventional data processing is solely based on information in the form of data. On the contrary, AI is based on knowledge, as well as, sets of instructions how to use the facts and information on how the individual facts are related1. It is a branch of information science whose objective is to endow machines with reasoning and perceptual capabilities2. Al systems fall into three categories. They are: Expert Systems, Natural Language Systems and Visual, Speech, Touch Perception Systems3. This article highlights the most successful area of development under AI, which is the Expert System (ESystem).